Pengaruh Pendapatan Asli Desa (PADES), Dana Desa (DD), Alokasi Dana Desa (ADD), Serta Bagi Hasil Pajak Dan Retribusi (BHPR) Terhadap Belanja Desa Bidang Pendidikan (Studi Kasus Di Desa Bringin, Kecamatan Wajak, Kabupaten Malang) - Irfan Saputra; Nurhidayah Nurhidayah; Etty Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study entitled the effect of Village Original Income (PADes), Village Funds (DD), Village Fund Allocation (ADD), and Revenue Sharing Taxes and Retribution (BHPR) on Village Expenditures in the Education Sector (Case Study in Bringin Village, Wajak District, Malang Regency). The purpose of this study was to identify the influence of PADes, DD, ADD, and BHPR on village spending on education in Bringin village, Wajak sub-district, Malang district. The independent variables in this study were PADes, DD, ADD, and BHPR, while the dependent variable was village spending on education. The object of this research is the village income and expenditure budget report (APBDes) starting from the 2015-2021 period. The data for this research are from the Bringin village office, Wajak sub-district, Malang district. The analysis technique used in this research is descriptive statistics, normality test, classical assumption test, and multiple linear regression test. In the interpretation of this research, it is shown that PADes, DD, and BHPR have a positive and significant influence on village spending on education. Meanwhile, ADD does not have a significant effect on village spending on education. Keyword : Village Original Inc ome (PADes), Village Funds (DD), Village Fund Allocation (ADD), and Tax and Retribution Revenue Sharing (BHPR) on Village Expenditures in the Education Sector.